Assessment of psychological well-being in stroke patients [Articol] - Santos, Carolina; Loureiro, Manuel; Carvalho, Paula; Gama, Jorge (CEP USM, 2022)
Stroke is one of the most common diseases worldwide with the most impact on patients' lives. The emergence of this sudden event has a significant impact when it comes to psychological well-being (PWB). The data we now present were obtained from a broader study of coping strategies and the assessment of PWB. In this poster, we take the opportunity to present the data obtained on the perception of PWB in victims of Stroke, assisted in the stroke units of two Portuguese reference district hospitals. To obtain these data, a sociodemographic questionnaire, a clinical form and the reduced version of the Psychological Well-Being Scales [1, 2] were applied. 159 individuals participated in this investigation, 94 males and 65 females, with a mean age of 66.35 years. The main results obtained show statistically significant differences in PWB as a function of age, gender, marital status and educational attainment. From these data, we draw implications for a better adequacy of psychological interventions with people who are victims of stroke. The increasing incidence of this pathology implies a more active promotion in terms of Psychological health, so that survivors can perceive the benefit of using adaptive behaviors that promote greater PWB in their lives.

Accidentul vascular cerebral este una dintre cele mai frecvente boli la nivel mondial, cu cel mai mare impact asupra vieții pacienților. Apariția acestui eveniment brusc are un impact semnificativ atunci când vine vorba de bunăstarea psihologică (PWB). Datele pe care le prezentăm acum au fost obținute dintr-un studiu mai larg al strategiilor de coping și evaluarea PWB. În acest poster, profităm de ocazie pentru a prezenta datele obținute cu privire la percepția PWB la victimele AVC, asistate în unitățile de AVC din două spitale raionale de referință portugheze. Pentru obținerea acestor date s-au aplicat un chestionar socio-demografic, o formă clinică și versiunea redusă a Scalelor de bunăstare psihologică [1, 2]. La această anchetă au participat 159 de persoane, 94 de bărbați și 65 de femei, cu o vârstă medie de 66,35 ani. Principalele rezultate obținute arată diferențe semnificative statistic în PWB în funcție de vârstă, sex, stare civilă și nivel de educație. Din aceste date, tragem implicații pentru o mai bună adecvare a intervențiilor psihologice cu persoanele care sunt victime ale accidentului vascular cerebral. Incidența tot mai mare a acestei patologii presupune o promovare mai activă în ceea ce privește sănătatea psihologică, astfel încât supraviețuitorii să poată percepe beneficiul utilizării unor comportamente adaptative care promovează un PWB mai mare în viața lor.
EVALUAREA BUNĂSTĂRII PSIHOLOGICE LA PACIENȚI CU AVC
Keywords: Stroke patients; psychological well-being; coping strategies; psychological interventions; statistically significant differences; psychological health; accident vascular cerebral; bunăstare psihologică; strategii de coping; intervenții psihologice; diferențe statistic semnificative; sănătate psihologică